Composite absorbent for eliminating odor of sewage sludge and preparation method of composite absorbent

By using composite absorbers of natural mineral materials such as bentonite, limestone, hematite and chemical absorbers such as zinc chloride, the high cost and secondary pollution problems in the treatment of sewage sludge odor are solved, and efficient and environmentally friendly pollution is achieved. Mud odor removal effect.

CN119281291APending Publication Date: 2025-01-10HUBEI JIADE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411584647.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has the disadvantages of high cost, complex operation, limited effect or secondary pollution in eliminating sewage and sludge odor, and it is difficult to be widely promoted in large-scale applications.

Method used

Using a composite absorber composed of bentonite, limestone, hematite and zinc chloride, nickel oxide, sodium persulfate, and titanium silicon molecular sieve, it can absorb and decompose pollution efficiently through the adsorption characteristics of natural mineral materials and the decomposition ability of chemical absorbers. Hydrogen sulfide, ammonia and volatile organic matter in the mud.

Benefits of technology

It has achieved efficient, low-cost and environmentally friendly sludge odor removal, avoided secondary pollution, and is suitable for large-scale sewage treatment plants and sludge compost yards, with good stability and economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281291A_ABST
    Figure CN119281291A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of stink absorbents, and particularly provides a composite absorbent for eliminating stink of sewage and sludge and a preparation method of the composite absorbent. The composite absorbent is formed by compounding a plurality of natural mineral materials and a chemical absorbent according to a specific proportion, and can efficiently absorb and decompose stink components such as hydrogen sulfide, ammonia gas and volatile organic compounds in sludge. The preparation method comprises the following steps: sequentially airing, drying, crushing, screening and oxidizing and activating various natural mineral materials, then mixing and stirring with various chemical absorbents according to a certain ratio, and finally carrying out ball milling treatment to obtain the composite absorbent with efficient absorption and decomposition capabilities. The composite absorbent not only can effectively eliminate stink emitted by sludge, but also has safe and environment-friendly components, does not cause secondary pollution to the environment, is simple in preparation process and low in cost, is particularly suitable for the fields of urban domestic sewage treatment plants, sludge composting and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of odor absorbents, and in particular to a composite absorbent for eliminating the odor of sewage sludge and a preparation method thereof. Background Art

[0002] Urban domestic sewage sludge contains abundant organic matter and water, and often emits unpleasant odorous gases. The main components of these gases include hydrogen sulfide, ammonia and various volatile organic compounds (VOCs), which not only cause serious damage to the atmospheric environment, but also pose a threat to the quality of life and health of surrounding residents. At present, a variety of technical means have been proposed to deal with the sludge odor problem, including physical closure, chemical spraying and biological deodorization.

[0003] However, these methods often have the disadvantages of high cost, complex operation, limited effect or secondary pollution, and are difficult to be widely promoted in practical applications. For example, the physical sealing method blocks the diffusion of malodorous gases by sealing the sludge. Although it can control the spread of odor to a certain extent, it cannot fundamentally eliminate the generation of malodorous gases. In addition, the construction and maintenance costs of closed facilities are high, especially in large-scale sewage treatment plants, and it is difficult to operate effectively for a long time. The chemical spraying method uses chemical agents to spray directly on the surface of the sludge to neutralize or cover up the malodorous gases. This method is simple to operate, but the sustainability of the spraying agent is poor and requires frequent replenishment. In addition, some chemical agents may have adverse effects on the environment or the subsequent treatment of the sludge, and are prone to secondary pollution risks. The biological deodorization method uses the metabolism of microorganisms to decompose malodorous substances and has good environmental protection. However, biological methods often require strict operating conditions, including temperature, humidity and the living environment of microorganisms, and are complex to manage. In addition, the treatment effect of high-concentration malodorous gases is not ideal. In addition, since the activity of microorganisms is greatly affected by the environment, the stability and reliability of biological deodorization are difficult to guarantee, and its application in large-scale sludge treatment still has certain limitations.

[0004] In view of the above-mentioned deficiencies of the prior art, the present invention proposes a composite absorbent based on natural mineral materials and chemical absorbents. By combining the adsorption characteristics of various natural mineral materials and the strong decomposition ability of chemical absorbents, the absorbent can efficiently absorb and decompose hydrogen sulfide, ammonia and volatile organic compounds in sludge, and fundamentally eliminate odor. At the same time, the preparation process of the composite absorbent is simple, the cost is low, the raw materials are safe and environmentally friendly, and it will not cause secondary pollution to the environment, and has good application prospects. Summary of the invention

[0005] The object of the present invention is to provide a composite absorbent for eliminating the malodor of sewage sludge and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the defects of the prior art, the present invention adopts the following technical solutions:

[0007] A composite absorbent for eliminating the stench of sewage sludge, the composite absorbent being composed of the following weight percentages of natural mineral materials and chemical absorbent components:

[0008] a) Natural mineral materials:

[0009] ①. Bentonite: 30-50%wt,

[0010] ②.Limestone: 20-30%wt,

[0011] ③.Hematite: 5-15%wt,

[0012] b) Chemical absorbent:

[0013] ①. Zinc chloride: 2-10%wt,

[0014] ②. Nickel oxide: 2-10%wt,

[0015] ③.Sodium persulfate: 2-10%wt,

[0016] ④. Titanium silicate molecular sieve: 2-10%wt.

[0017] Preferably, the bentonite, limestone and hematite raw materials need to be pretreated by steps such as air drying, crushing and screening, and oxidation activation.

[0018] Preferably, in the air-drying step, the bentonite, limestone and hematite raw materials need to be air-dried until the moisture content is less than 10%.

[0019] Preferably, in the crushing and screening step, the dried bentonite, limestone and hematite need to be crushed and screened to finenesses of 100-200 mesh, 50-100 mesh and 25-75 mesh respectively.

[0020] Preferably, in the oxidation activation step, the bentonite, limestone and hematite powders need to be oxidized and activated for 3-8 hours in a continuous and sufficient air atmosphere and a temperature of 150-300°C.

[0021] Preferably, the composite absorbent is prepared by the following steps:

[0022] 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 10%, and then setting them aside;

[0023] 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside;

[0024] 3) oxidizing and activating bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 150-300° C. for 3-8 hours, and then setting aside;

[0025] 4) Mixing the activated natural mineral material powder (bentonite, limestone, hematite) and the chemical absorbent (zinc chloride, nickel oxide, sodium persulfate, titanium silicon molecular sieve) in a specific ratio and stirring them evenly, and then setting them aside;

[0026] 5) ball milling the mixed powder material obtained in step 4) to finally obtain a composite absorbent.

[0027] Preferably, in step 4), the mixing ratio of each component is: 30-50 parts of activated bentonite powder, 20-30 parts of activated limestone powder, 5-15 parts of activated hematite powder, 2-10 parts of zinc chloride, 2-10 parts of nickel oxide, 2-10 parts of sodium persulfate, and 2-10 parts of titanium silicon molecular sieve.

[0028] Preferably, in step 5), the conditions for ball milling are: the ball-to-material ratio is constant at 8:1, and the ball milling time is 30-90 minutes.

[0029] Preferably, the composite absorbent is kept cool and dry during storage to avoid contact with moisture and strong acid.

[0030] Preferably, the composite absorbent is added in an amount of 5-10 grams per ton of untreated raw sewage sludge (water content greater than 95%).

[0031] Compared with the existing technology, the composite absorbent of the present invention has the following beneficial effects in terms of technological innovation and practical application:

[0032] (1) Efficient absorption and decomposition of malodorous components in sludge. The composite absorbent provided by the present invention can effectively adsorb and decompose the main malodorous components in sludge, such as hydrogen sulfide, ammonia and volatile organic compounds (VOCs), by rationally mixing a variety of natural mineral materials and chemical absorbents. Natural mineral materials (such as bentonite, limestone and hematite) have strong adsorption properties and can quickly capture and fix malodorous gases. Chemical absorbents (such as zinc chloride, nickel oxide, sodium persulfate and titanium silicon molecular sieves) decompose malodorous components into harmless substances through chemical reactions. This combination of dual effects makes the composite absorbent show remarkable efficiency in treating sludge odor problems.

[0033] (2) The preparation process is simple and the cost is low. The preparation process of the composite absorbent of the present invention is relatively simple, and it can be completed only through the steps of drying, crushing, activating, mixing and ball milling of the raw materials. The required equipment and operating conditions are not complicated, and it is easy to realize industrial production. In addition, the main components of the composite absorbent are natural mineral materials, which are widely available and inexpensive, making the overall production cost low. Therefore, while meeting the demand for efficient deodorization, the present invention has strong market competitiveness and is particularly suitable for large-scale application in scenes such as urban sewage treatment plants and sludge composting sites.

[0034] (3) Environmentally friendly, no secondary pollution. The natural mineral materials and chemical absorbents selected in the present invention are environmentally friendly raw materials and will not generate secondary pollution during use. For example, bentonite and limestone are not only harmless to the environment, but can also be further recycled as soil conditioners. At the same time, the impact of zinc chloride, nickel oxide and other substances used in chemical absorbents on the environment is controllable at low dosages and has no residual toxicity. In addition, no toxic solvents or other polluting substances are required in the preparation process, and the overall operation process is green and environmentally friendly. Therefore, the present invention can effectively avoid the risk of secondary environmental pollution while ensuring the deodorization effect, and meets modern environmental protection standards.

[0035] (4) Strong stability and wide application range. The natural mineral materials after oxidation activation treatment have good chemical stability and structural strength. In practical applications, they are not easily affected by changes in the external environment and can maintain the deodorization effect for a long time. At the same time, the composite absorbent of the present invention has good adsorption and decomposition capabilities for a variety of malodorous gases and is suitable for a variety of complex sludge treatment scenarios, especially in high temperature and high humidity environments such as sludge composting sites or urban sewage treatment plants. It shows good effects. In addition, the use of ball milling technology makes the particle size of the composite absorbent uniform, further improving its operability and deodorization effect in practical applications.

[0036] (5) Small dosage and outstanding economy. In actual use, the composite absorbent of the present invention only needs 5-10 grams per ton of sewage sludge as the unit dosage to effectively control the generation of odor. Compared with the high dosage requirements of other deodorants on the market, the absorbent of the present invention greatly reduces the operating cost through low-dose dosage while ensuring excellent performance, further improving its economy. This advantage makes the present invention more suitable for large-scale urban sewage treatment and sludge treatment scenarios, and can reduce treatment costs while ensuring the stability and sustainability of the treatment effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention provides a preparation flow chart of a composite absorbent for eliminating the stench of sewage sludge.

[0038] Figure 2A comparison chart of the purification efficiency of several composite absorbents provided by the present invention and two other absorbents on sludge odor components. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings and other related contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments listed in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] On the one hand, one of the purposes of the embodiments of the present invention is to provide a composite absorbent for eliminating the stench of sewage sludge, wherein the composite absorbent is composed of the following weight percentages of natural mineral materials and chemical absorbent components:

[0041] a) Natural mineral materials:

[0042] ①. Bentonite: 30-50%wt,

[0043] ②.Limestone: 20-30%wt,

[0044] ③.Hematite: 5-15%wt,

[0045] b) Chemical absorbent:

[0046] ①. Zinc chloride: 2-10%wt,

[0047] ②. Nickel oxide: 2-10%wt,

[0048] ③.Sodium persulfate: 2-10%wt,

[0049] ④. Titanium silicate molecular sieve: 2-10%wt.

[0050] Furthermore, the bentonite, limestone and hematite raw materials need to be pre-treated by steps such as air drying, crushing and screening, and oxidation activation.

[0051] Furthermore, in the air-drying step, the bentonite, limestone and hematite raw materials need to be air-dried until the moisture content is less than 10%.

[0052] Furthermore, in the crushing and screening step, the dried bentonite, limestone and hematite need to be crushed and screened to finenesses of 100-200 mesh, 50-100 mesh and 25-75 mesh respectively.

[0053] Furthermore, in the oxidation activation step, the bentonite, limestone and hematite powders need to be oxidized and activated for 3-8 hours in a continuous and sufficient air atmosphere and a temperature of 150-300°C.

[0054] On the other hand, see Figure 1 , the composite absorbent is prepared by the following steps:

[0055] 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 10%, and then setting them aside;

[0056] 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside;

[0057] 3) oxidizing and activating bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 150-300° C. for 3-8 hours, and then setting aside;

[0058] 4) Mixing the activated natural mineral material powder (bentonite, limestone, hematite) and the chemical absorbent (zinc chloride, nickel oxide, sodium persulfate, titanium silicon molecular sieve) in a specific ratio and stirring them evenly, and then setting them aside;

[0059] 5) ball milling the mixed powder material obtained in step 4) to finally obtain a composite absorbent.

[0060] Furthermore, in step 4), the mixing ratio of each component is: 30-50 parts of activated bentonite powder, 20-30 parts of activated limestone powder, 5-15 parts of activated hematite powder, 2-10 parts of zinc chloride, 2-10 parts of nickel oxide, 2-10 parts of sodium persulfate, and 2-10 parts of titanium silicon molecular sieve.

[0061] Furthermore, in the step 5), the conditions for ball milling are: the ball-to-material ratio is constant at 8:1, and the ball milling time is 30-90 minutes.

[0062] Furthermore, the composite absorbent is kept cool and dry during storage to avoid contact with moisture and strong acid.

[0063] Furthermore, the dosage of the composite absorbent is 5-10 grams per ton of untreated raw sewage sludge (water content greater than 95%).

[0064] In the following embodiments, the bentonite, limestone and hematite raw materials used are all purchased from a chemical group in Wuhan. The test results of their main chemical components are shown in Table 1, Table 2 and Table 3, respectively. The zinc chloride, nickel oxide, sodium persulfate and titanium silicon molecular sieve used are all industrial grade products with a content greater than 99%.

[0065] Table 1 Main chemical composition of bentonite raw materials / %wt

[0066] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> MgO CaO <![CDATA[Na2O]]> <![CDATA[K2O]]> other 62.36 24.47 6.78 1.59 3.25 0.65 0.58 0.32

[0067] Table 2 Main chemical composition of limestone raw materials / %wt

[0068] <![CDATA[CaCO3]]> MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> other 97.35 1.43 0.35 0.23 0.31 0.08 0.07 0.18

[0069] Table 3 Main chemical composition of hematite raw materials / %wt

[0070] <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[MnO2]]> other 72.36 13.80 7.88 1.76 1.35 1.47 1.11 0.27

[0071] Example 1

[0072] 1. Preparation of composite absorbent:

[0073] 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 3%, and then setting them aside;

[0074] 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside;

[0075] 3) oxidizing and activating bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 180° C. for 5 hours, and then setting aside;

[0076] 4) Mixing the activated natural mineral material powder (45 parts of bentonite, 25 parts of limestone, 10 parts of hematite) and chemical absorbent (5 parts of zinc chloride, 5 parts of nickel oxide, 5 parts of sodium persulfate, 5 parts of titanium silicon molecular sieve) in a specific ratio and stirring evenly, and then setting aside;

[0077] 5) The mixed powder material obtained in step 4) was ball-milled for 60 minutes to finally obtain a composite absorbent.

[0078] 2. Verification of the effect of composite absorbent:

[0079] The composite absorbent prepared by Example 1 was used to verify the effect in a certain urban sewage treatment plant in Wuhan. The amount of the composite absorbent was 7 grams per ton of untreated raw sewage sludge (water content greater than 98%). According to DB31 / 982-2016 urban sewage treatment plant air pollutant emission standards, the enterprise boundary pollutant concentration of the sewage treatment plant before and after the composite absorbent was put into use was monitored, and the monitored pollutants included ammonia, hydrogen sulfide, volatile organic compounds (methyl mercaptan, methane) and odor concentration. Among them, the types of pollutants monitored, concentration units and monitoring locations are shown in Table 4.

[0080] Table 4 Types of pollutants monitored, concentration units and monitoring locations

[0081]

[0082] According to the monitoring results of pollutant concentration, the purification efficiency of the composite absorbent for various pollutants is defined as the concentration of pollutants before the composite absorbent is used minus the concentration of pollutants after the composite absorbent is used, divided by the concentration of pollutants before the composite absorbent is used. The higher the purification efficiency, the better the effect of eliminating odor.

[0083] Example 2

[0084] 1. Preparation of composite absorbent:

[0085] 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 3%, and then setting them aside;

[0086] 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside;

[0087] 3) oxidizing and activating bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 200° C. for 4 hours, and then setting aside;

[0088] 4) Mixing the activated natural mineral material powder (43 parts of bentonite, 28 parts of limestone, 12 parts of hematite) and chemical absorbent (3 parts of zinc chloride, 5 parts of nickel oxide, 3 parts of sodium persulfate, 6 parts of titanium silicon molecular sieve) in a specific ratio and stirring evenly, and then setting aside;

[0089] 5) The mixed powder material obtained in step 4) was ball-milled for 45 minutes to finally obtain a composite absorbent.

[0090] 2. Verification of the effect of composite absorbent:

[0091] The method is basically the same as Example 1, with the main difference being that the dosage of the composite absorbent is 8 grams per ton of untreated raw sewage sludge (water content greater than 98%).

[0092] Example 3

[0093] 1. Preparation of composite absorbent:

[0094] 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 3%, and then setting them aside;

[0095] 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside;

[0096] 3) oxidizing and activating the bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 230° C. for 3.5 hours, and then setting aside;

[0097] 4) Mixing the activated natural mineral material powder (39 parts of bentonite, 27 parts of limestone, and 13 parts of hematite) and chemical absorbent (8 parts of zinc chloride, 3 parts of nickel oxide, 6 parts of sodium persulfate, and 4 parts of titanium silicon molecular sieve) in a specific ratio and stirring them evenly, and then setting them aside;

[0098] 5) The mixed powder material obtained in step 4) was ball-milled for 40 minutes to finally obtain a composite absorbent.

[0099] 2. Verification of the effect of composite absorbent:

[0100] The method is basically the same as Example 1, with the main difference being that the dosage of the composite absorbent is 6 grams per ton of untreated raw sewage sludge (water content greater than 98%).

[0101] Comparative Example 1

[0102] This comparative example uses a water-based absorbent purchased from an environmental protection company in Tianjin, with the dosage being 20 grams per ton of untreated raw sewage sludge (water content greater than 98%).

[0103] Comparative Example 2

[0104] This comparative example uses a sodium-based absorbent purchased from an environmental protection company in Shanghai, with the dosage being 20 grams per ton of untreated raw sewage sludge (water content greater than 98%).

[0105] Odor purification efficiency comparison:

[0106] See also Figure 2 Through the testing and comparative analysis of different embodiments, the composite absorbent provided by the present invention shows significant advantages in the purification of sludge malodorous gas, especially in terms of ammonia, hydrogen sulfide, methyl mercaptan, methane and comprehensive odor concentration, and has higher purification efficiency and lower operating cost. The following is a comparative analysis of three embodiments of the present invention and their comparative examples.

[0107] In Example 1, the composite absorbent provided by the present invention was added at 7 grams per ton of untreated raw sewage sludge (water content greater than 98%), and the purification efficiency of ammonia, hydrogen sulfide, methyl mercaptan, methane and odor concentration reached 99.87%, 99.79%, 99.63%, 99.25% and 99.44% respectively. This result shows that the composite absorbent of the present invention can still significantly reduce the concentration of multiple malodorous gases at a lower dosage, achieving a nearly complete purification effect.

[0108] In Example 2, the composite absorbent provided by the present invention was added at 8 grams per ton of untreated raw sewage sludge, and the purification efficiency of ammonia, hydrogen sulfide, methyl mercaptan, methane and odor concentration reached 99.68%, 99.45%, 99.89%, 99.36% and 99.26% respectively. This example shows that slightly increasing the amount of the composite absorbent can further improve the efficiency in certain gas purification aspects, especially in the purification of methyl mercaptan, reaching 99.89% efficient purification, indicating that the composite absorbent of the present invention has extremely high absorption and purification capabilities for sulfur-containing odorous gases.

[0109] In Example 3, the composite absorbent provided by the present invention was added at 6 grams per ton of untreated raw sewage sludge, and the purification efficiency of ammonia, hydrogen sulfide, methyl mercaptan, methane and odor concentration reached 99.36%, 99.48%, 99.81%, 99.28% and 99.84%, respectively. This example shows that even at a lower dosage, the composite absorbent of the present invention can still achieve extremely high purification efficiency, especially in the purification of comprehensive odor concentration, reaching 99.84%, proving that the absorbent of the present invention has a strong comprehensive purification ability when multiple odorous gases exist at the same time.

[0110] However, the water-based absorbent provided in Comparative Example 1 and the sodium-based absorbent provided in Comparative Example 2 are both added at 20 grams per ton of untreated raw sewage sludge, which is much higher than the amount of the composite absorbent of the present invention. In addition, the purification efficiency of the water-based absorbent for ammonia, hydrogen sulfide, methyl mercaptan, methane and odor concentrations is only 63.45%, 42.82%, 36.94%, 69.87%, 53.36%; the purification efficiency of the sodium-based absorbent is 76.48%, 75.39%, 23.58%, 53.69%, 66.97% respectively.

[0111] From the perspective of purification efficiency, both water-based absorbents and sodium-based absorbents are significantly inferior to the composite absorbent of the present invention in the purification of all malodorous gases. In particular, in the purification of hydrogen sulfide and methyl mercaptan, the effects of water-based absorbents and sodium-based absorbents are particularly unsatisfactory, and can only achieve purification efficiencies of 42.82% and 23.58%, respectively, which are far lower than the purification efficiencies of nearly 100% in the embodiments provided by the present invention.

[0112] The composite absorbent provided by the present invention exhibits excellent odor gas purification efficiency at a relatively low dosage, especially in the purification of odor components such as ammonia, hydrogen sulfide and methyl mercaptan, achieving an almost complete purification effect. This high purification performance gives the composite absorbent of the present invention a significant advantage in the field of sewage sludge treatment.

[0113] 1. High-efficiency purification capability. Whether it is ammonia, hydrogen sulfide, methyl mercaptan or methane, the composite absorbent of the present invention can achieve a purification efficiency close to 100% at a very low dosage, especially in Example 2, the purification efficiency of methyl mercaptan reaches 99.89%, indicating that the absorbent has extremely high selectivity and adsorption capacity.

[0114] 2. Lower dosage: Compared with the comparative example, which requires up to 20 grams of absorbent per ton of sludge, the composite absorbent of the present invention only requires 6-8 grams to achieve a better purification effect, greatly reducing the material cost in actual operation.

[0115] 3. Superior comprehensive performance. The composite absorbent of the present invention exhibits stable and efficient performance in the purification of different malodorous gases, especially in the presence of a mixture of multiple gases, and can still maintain nearly 100% efficient purification, making the technology widely applicable in practical applications.

[0116] 4. Significant economic benefits. By reducing the amount of absorbent, the present invention can not only reduce material costs, but also reduce the risk of secondary pollution in the sewage sludge treatment process and improve economic benefits. This has important application value for large sewage treatment plants or other industrial facilities that need to treat a large amount of sludge.

[0117] Therefore, the application of the composite absorbent of the present invention in sludge treatment has obvious technical advantages and economic benefits. Its high efficiency and low cost make it have a wide application prospect in the field of sewage sludge treatment and can make positive contributions to industrial production and environmental protection.

[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the general premise of the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite absorbent for eliminating the stench of sewage sludge, characterized in that: The composite absorbent is composed of the following natural mineral materials and chemical absorbent components in the following weight percentages: a) Natural mineral materials: ①. Bentonite: 30-50%wt, ②.Limestone: 20-30%wt, ③.Hematite: 5-15%wt, b) Chemical absorbent: ①. Zinc chloride: 2-10%wt, ②. Nickel oxide: 2-10%wt, ③.Sodium persulfate: 2-10%wt, ④. Titanium silicate molecular sieve: 2-10%wt.

2. The composite absorbent according to claim 1, characterized in that: The bentonite, limestone and hematite raw materials need to be pre-treated by air drying, crushing, screening and oxidation activation.

3. The composite absorbent according to claim 1, characterized in that: In the air-drying step, the bentonite, limestone and hematite raw materials need to be air-dried until the moisture content is less than 10%.

4. The composite absorbent according to claim 1, characterized in that: In the crushing and screening step, the dried bentonite, limestone and hematite need to be crushed and screened to finenesses of 100-200 mesh, 50-100 mesh and 25-75 mesh respectively.

5. The composite absorbent according to claim 1, characterized in that: In the oxidation activation step, the bentonite, limestone and hematite powders need to be oxidized and activated for 3-8 hours in a continuous and sufficient air atmosphere and a temperature of 150-300° C.

6. The composite absorbent according to any one of claims 1 to 5, characterized in that: The composite absorbent is prepared by the following steps: 1) Drying the natural mineral materials bentonite, limestone and hematite raw materials in the sun until the moisture content is less than 10%, and then setting them aside; 2) crushing and sieving the dried bentonite, limestone and hematite to 100-200 mesh, 50-100 mesh and 25-75 mesh respectively, and then setting aside; 3) oxidizing and activating bentonite, limestone and hematite powders in a continuous and sufficient air atmosphere at a temperature of 150-300° C. for 3-8 hours, and then setting aside; 4) mixing the activated natural mineral material powder with the chemical absorbent and stirring them evenly, and then setting them aside; 5) ball milling the mixed powder material obtained in step 4) to finally obtain a composite absorbent.

7. The preparation method according to claim 6, characterized in that: In the step 4), the mixing ratio of each component is: 30-50 parts of activated bentonite powder, 20-30 parts of activated limestone powder, 5-15 parts of activated hematite powder, 2-10 parts of zinc chloride, 2-10 parts of nickel oxide, 2-10 parts of sodium persulfate, and 2-10 parts of titanium silicon molecular sieve.

8. The preparation method according to claim 6, characterized in that: In the step 5), the conditions for ball milling are: the ball-to-material ratio is constant at 8:1, and the ball milling time is 30-90 minutes.

9. The preparation method according to claim 6, characterized in that: The composite absorbent should be kept cool and dry during storage and should be avoided from contact with moisture and strong acid.

10. The preparation method according to claim 6, characterized in that: The dosage of the composite absorbent is 5-10 grams per ton of untreated raw sewage sludge, wherein the water content of the raw sewage sludge is greater than 95%.